Lost-ore mining:a supplementary mining method to sublevel caving - Zhang, Z.-X. (Zong-Xian) (Elsevier, 2023)
Abstract Sublevel caving (SLC) is a mass mining method having high productivity and high safety. However, this method often causes a considerable amount of permanent ore loss. Interestingly, all lost ores are buried in the broken waste rocks that come mostly from the caved hanging wall and partly from the ore body in which ore and waste rock are originally situated together. To mine out such lost ores from the broken waste rocks and increase ore recovery in SLC mines, a new mining method called lost-ore mining is introduced as a supplementary method to SLC, and a simple mechanics analysis is used to explain why the lost-ore could be mined out. Using this lost ore mining method, the Malmberget mine had recovered 7.5 million tons of lost iron ores from many old production drifts, as reported in the year 2016. Similarly, the Kiruna mine had mined out 2.6 million tons of iron ores from the old production drifts, according to a report in 2012. At last, some suggestions on how to use this new method are proposed.